2018
DOI: 10.1021/acs.est.7b04449
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on Ecosystem Mercury Cycling Revealed by Stable Isotopes of Mercury in Water Flowing from a Headwater Peatland Catchment

Abstract: Stable isotope compositions of mercury (Hg) were measured in the outlet stream and in soil cores at different landscape positions in a 9.7-ha boreal upland-peatland catchment. An acidic permanganate/persulfate digestion procedure was validated for water samples with high dissolved organic matter (DOM) concentrations through Hg spike addition analysis. We report a relatively large variation in mass-dependent fractionation (δHg; from -2.12 to -1.32‰) and a smaller, but significant, variation of mass-independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 47 publications
6
59
1
Order By: Relevance
“…The isotopic composition of Hg in tree rings from the modern era (1951–2014) in both deciduous and coniferous species in this study is broadly similar to the Hg isotopic composition typically observed in North American foliage (Demers et al, ; Olson et al, ; Woerndle et al, ; Zheng et al, ) (Figure S5 and Tables S3 and S4). This is consistent with bole wood Hg being derived predominantly from atmospheric gaseous Hg that accumulates in foliage and is subsequently translocated downward via the phloem (e.g., Arnold et al, ).…”
Section: Discussionsupporting
confidence: 82%
“…The isotopic composition of Hg in tree rings from the modern era (1951–2014) in both deciduous and coniferous species in this study is broadly similar to the Hg isotopic composition typically observed in North American foliage (Demers et al, ; Olson et al, ; Woerndle et al, ; Zheng et al, ) (Figure S5 and Tables S3 and S4). This is consistent with bole wood Hg being derived predominantly from atmospheric gaseous Hg that accumulates in foliage and is subsequently translocated downward via the phloem (e.g., Arnold et al, ).…”
Section: Discussionsupporting
confidence: 82%
“…Hg(II) undergoes photoreduction in cloud droplets and surface waters, which imparts negative Δ 199 Hg values in the produced Hg(0) and positive Δ 199 Hg values in residue Hg(II) (Bergquist & Blum, ; Gratz et al, ). Soils with less influences from local industrial Hg contamination, which primarily accumulate Hg(0), have been shown negative Δ 199 Hg (−0.29 ± 0.12‰, σ, n = 156) and lower δ 202 Hg values (−1.82 ± 0.39‰, σ, n = 156) (Biswas et al, ; Demers et al, ; Jiskra et al, 2017; Wang et al, ; Woerndle et al, ; Zhang et al, ; Zheng et al, ). Because soils and vegetation accumulate Hg(0) with lower δ 202 Hg and negative Δ 199 Hg values, the Hg(II) species in the atmosphere should be characterized by higher δ 202 Hg and positive Δ 199 Hg values.…”
Section: Resultsmentioning
confidence: 99%
“… Triple mixing of industrial, watershed, and atmospheric Hg for sediment cores. The solid red circle ① represents industrial Hg ( δ 202 Hg: −0.53 ± 0.51‰; Δ 199 Hg: −0.02 ± 0.11‰; σ, n = 481) (Balogh et al, ; Cooke et al, ; Donovan et al, ; Gray et al, ; Guédron et al, ; Ma et al, ; Mil‐Homens et al, ; Sonke et al, ; Yin et al, ); the solid yellow circle ② represents soils collected from pristine sites ( δ 202 Hg: −1.82 ± 0.39‰; Δ 199 Hg: −0.29 ± 0.12‰; σ, n = 156) (Biswas et al, ; Demers et al, ; Jiskra et al, 2017; Wang et al, ; Woerndle et al, ; Zhang et al, ; Zheng et al, ); the blue dashed circle ③ represents precipitations ( δ 202 Hg: −1.22 ± 1.08‰; Δ 199 Hg: 0.38 ± 0.33‰; σ, n = 117) (Chen et al, ; Demers et al, ; Gratz et al, ; Sherman et al, ; Wang et al, ; Yuan et al, ); and the solid blue circle ④ represents precipitation‐derived Hg with a shift of −0.6‰ in δ 202 Hg.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2008) found that spring snowmelt period accounted for 26–39% of annual THg export from the peatland watershed. Upland runoff and dry deposition can be major sources of Hg to streams that drain peatlands (Kolka, Grigal, Verry, & Nater, 1999a,b; Woerndle et al., 2018). Also, lateral runoff of bog water (Verry et al., 2011b) will similarly connect Hg from atmospheric deposition when near‐surface bog water radially flows to a surrounding lagg and then to an outlet stream.…”
Section: Discussionmentioning
confidence: 99%